Wideband-Efficient SOI Uniform Subwavelength Grating Couplers by Effective-Index and Leakage-Factor Matching at Multiple Wavelengths - Wanzhen Hu; Huang Shiyuan; Citrin Scott David; Hao Long; Chunyong Yang; Shaoping Chen; Jin Hou (IEEE Photonics Journal)
By improving both effective-index (EI) matching and leakage-factor (LF) matching at multiple wavelengths, a method to achieve a wideband-efficient uniform subwavelength grating coupler (SWGC) has been theoretically demonstrated. First, the root-mean-square-error between the grating EI and ideal EI (RMSE-EI) and root-mean-square-error between the grating LF and ideal LF (RMSE-LF) are adopted to weigh EI and LF matching at multiple wavelengths. It is found that when the RMSE-EI decreases and keeping RMSE-LF almost constant, the coupling bandwidth of the uniform SWGC could be substantially increased. Moreover, when RMSE-LF of the uniform SWGC decreases while RMSE-EI remains almost constant, the overall integral coupling efficiency (ICE) within the band from 1525 nm to 1575 nm is enhanced. Furthermore, by simultaneously enhancing both EI matching and LF matching at three wavelengths, a 1-dB bandwidth of 53.7 nm and ICE of 22.31 is obtained in an optimized SOI uniform SWGC. Using the proposed multi-wavelength optimizing methodology, even more efficient wideband couplers could be expected by adopting more optimization accounting for more structural parameters in the future.